Multifraction Radiotherapy for Palliation of Painful Bone Metastases: 20 Gy versus 30 Gy. Issue 3 (May 2015) - Valeriani, Maurizio; Scaringi, Claudia; Blasi, Luciana; Carnevale, Alessia; De Sanctis, Vitaliana; Bonome, Paolo; Bracci, Stefano; Marrone, Gianluca; Minniti, Giuseppe; Enrici, Riccardo Maurizi
Aims and Background: To compare 2 multifraction radiotherapy schedules in the palliation of painful bone metastases. Methods and Study Design: We retrospectively analyzed clinical data of 105 patients with a total of 140 painful bone metastases who were treated with 20 Gy in 5 fractions or 30 Gy in 10 fractions. The primary tumors were breast (30%), lung (28%), and prostate (14%). The main sites of irradiation were spine (n = 79) and sacrum or pelvis (n = 39). Pain was graded by patients according to the pain numeric rating scale just before and 1 month after radiotherapy. Pain progression was defined as an increase ≥2 on pain scale after an initial response. Results: The overall response rate at 1 month was 88.6%. Overall response rate was 89.6% in the 20-Gy arm and 87.3% in the 30-Gy arm (p = 0.669). The rate of complete response was statistically better in patients treated with 30 Gy (p = 0.019). The mean reduction in pain was 3.2 in the 20-Gy group and 3.6 in the 30-Gy group. Pain progression was 6.5% and 1.6%, respectively. The incidence of acute toxicity was statistically significantly higher in the 30-Gy arm (23.8%) than in the 20-Gy arm (2.6%) (p = 0.001). One pathologic fracture of the irradiated bone was observed in the 30-Gy arm. Two lesions, one in each group, were re-irradiated for pain recurrence. Pain progression was found in 6.5% of the irradiated lesions in the 20-Gy arm and in 1.6% in the 30-Gy arm. Conclusions: In our series, both regimens achieved high rate of pain relief, although the group treated with higher total dose reported better complete response rate. The 30-Gy arm had a significantly higher rate of acute toxicity.